Effect of methanol leaf extract of Dalbergia saxatilis Hook.f (fabaceae) on renal function - Hassan, Fatima Ismail (Avicenna J Phytomed, 2016)
OBJECTIVE: Dalbegia saxatilis (D.saxatilis) is used as a decoction in traditional medicine for ailments such as cough, small pox, skin lesions, bronchial ailments and toothache. This study is aimed at evaluating the toxic effect of methanol leaf extract of D.saxatilis on renal function. MATERIALS AND METHODS: Wistar rats of both sexes were divided into four groups of five: control animals (group 1) received distilled water 1 ml/kg while groups 2, 3 and 4 were given graded doses of the extract (250, 500 and 1000 mg/kg body weight, respectively) daily for 28 days. Body weight changes were estimated by weighing the rats twice weekly using digital weighing balance. After 28 days, blood samples were obtained for evaluation of renal indices and the kidney was used for histopathology. Data were analysed using one–way and repeated measures ANOVA using SPSS version 20. RESULTS: Significant weight increase in all groups were observed (p<0.05). Significant reduction in electrolytes concentration was observed following treatment with extract (250 and 500 mg/kg) (p<0.05). Histopathological findings of the kidney revealed massive necrosis of the glomerulus with tubular distortion and lymphocyte hyperplasia at 250 and 500 mg/kg while intense glomerular and tubular necrosis was observed at 1000 mg/kg of the extract. CONCLUSION: Since different doses of the extract caused reduction in electrolyte concentration and damage to the kidney it is suggested that prolonged administration of the extract is associated with increased risk of kidney toxicity.